Size effect on the flexural behavior of UHPFRC beams and RC beams strengthened with UHPFRC - Felipe Augusto da Silva Barbosa; Ramoel Serafini; Antonio Domingues de Figueiredo; Luís Antônio Guimarães Bitencourt Júnior (Revista IBRACON de Estruturas e Materiais)
Abstract The presence of fibers in Ultra-High-Performance Fiber Reinforced Concrete (UHPFRC) considerably affects the mechanical behavior of structural elements constructed from this material. While the flexural strength of traditional reinforced concrete beams is size-independent, this is not the case for UHPFRC. A numerical procedure based on cross-section equilibrium and compatibility is proposed here to parametrically investigate this size effect in both reinforced concrete beams strengthened with UHPFRC and pure UHPFRC beams. The flexural capacities computed using the numerical method agreed with those obtained experimentally from 14 experimental programs, with an average numerical-experimental ratio of 1.09 and a correlational coefficient of 0.94. Regarding the strengthened beams, the maximum flexural stresses were computed for three different strengthening layouts, considering heights from 100 to 2000 mm. As regards pure UHPFRC beams, the flexural strengths were computed for the same range of heights considering different fiber-volume ratios, as well as fiber lengths. The results show that three-side jacket beams are the most sensitive to the size effect, increasing the flexural strength of small members up to 697%. The beams strengthened on the compressive zone are the least sensitive, with an increase of 31% for the majority of beams. For pure UHPFRC beams, the results indicate that high fiber contents, such as 4%, led to a pronounced size effect, with increases in flexural strength of up to 1052% for the smallest beam compared to the concrete without fibers. Conversely, the use of 35 mm fibers instead of 13 mm attenuated the size effect, reducing the difference between the flexural strength of the smallest and the tallest members from 60 to 46%.